Migration and Financial Constraints: Evidence from Mexico - Manuela Angelucci (Institute for the Study of Labor (IZA), 2013)
Using data collected for the evaluation of the rural component of Oportunidades, Mexico's flagship anti-poverty program, I show that poor households' entitlement to an exogenous, temporary but guaranteed income stream increases US migration even if this income is mainly consumed and that some households likely use the entitlement to this income stream as collateral to finance the migration. The individuals who start migrating because of this income shock belong to households with no counterfactual US migrants, come from the middle of the local predicted wage distribution, and worsen migrant skills. These results suggest that financial constraints to international migration are binding for poor Mexicans, some of whom would like to migrate but cannot afford to. If generalizable, they indicate that, as growth and anti-poverty and micro-finance programs relax financial constraints for the poor, Mexican migration to the US will increase and higher levels of border enforcement will likely be needed.
Keywords: J61; O12; O15; F22; 330; migration; financial constraints; Mexico